2009
DOI: 10.1002/imhj.20204
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal physiological regulation is associated with perinatal factors: A study of neonates born to healthy African American women living in poverty

Abstract: Maternal mental health and prenatal stress are linked with neurobehavioral differences in the offspring. The majority of studies documenting this effect have been conducted using either predominantly European American infants or minority infants exposed to teratogens in utero. In this study, we focus on healthy African American women from low-income environments to investigate the earliest individual differences in biobehavioral regulation, including resting heart rate and variability (HRV). In 87 neonates, HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
2
22
0
1
Order By: Relevance
“…Although both of these studies were conducted with samples of full-term infants, it is possible that feeding route may be related to interaction quality for preterm infants as well. Previous research has also shown that full-term breastfed infants exhibit higher HRV and vagal tone, compared with full-term bottle fed infants (Butte, O’Brian Smith, & Garza, 1991; DiPietro, Larson, & Porges, 1987; Jacob, Byrne, & Keenan, 2009), suggesting possible differences in early infant physiological regulation related to feeding that may also predict interaction quality.…”
Section: Maternal Factorsmentioning
confidence: 98%
“…Although both of these studies were conducted with samples of full-term infants, it is possible that feeding route may be related to interaction quality for preterm infants as well. Previous research has also shown that full-term breastfed infants exhibit higher HRV and vagal tone, compared with full-term bottle fed infants (Butte, O’Brian Smith, & Garza, 1991; DiPietro, Larson, & Porges, 1987; Jacob, Byrne, & Keenan, 2009), suggesting possible differences in early infant physiological regulation related to feeding that may also predict interaction quality.…”
Section: Maternal Factorsmentioning
confidence: 98%
“…Findings in studies employing biomarkers of emotional SR also find that poorer rearing contexts can have a negative influence on children’s emotional SR (Jacob, Bryne, & Keenan, 2009; but see Blair et al, 2013, who did not find a relation between cumulative risk and children’s RSA).…”
Section: Associations Between Parent and Child Self-regulationmentioning
confidence: 99%
“…1921 In utero, maternal stress has an almost immediate impact on fetal ANS activity, and maternal chronic stress and depression predict neonate ANS activity. 22,23 High prenatal stress has been shown to predict blunted RSA recovery following the SFP in 6-month-old infants, with effects persisting into childhood. 2,3,24 In addition to prenatal influences, genetic factors and maternal experiences prior to pregnancy may also contribute to the development of the ANS.…”
Section: Intergenerational Influencesmentioning
confidence: 99%